ChemInform Abstract: A Base‐Catalyzed Cycloisomerization of 5‐Cyano‐Pentyne Derivatives: An Efficient Synthesis of 3‐Cyano‐4, 5‐dihydro‐1H‐pyrroles. Issue 12 (March 2015) - Meng, Jia; Li, Yi‐Jin; Zhao, Yu‐Long; Bu, Xiu‐Bin; Liu, Qun
Abstract The title reaction involves a tandem process providing access to 3‐cyano‐pyrrolines (II) and (IV) with 1, 3‐cyano migration as the key transformation.